DEVELOPMENT OF THE QUALITY MANAGEMENT SYSTEM OF INDUSTRIAL ENTERPRISES - THE MAIN FACTOR OF INCREASING THE COMPETITIVENESS OF PRODUCTS (World Economics and Finance Bulletin, 2022)
In this article are discussed the importance of developing a quality management system at improving the competitiveness of industrial products.
Keywords: industrial enterprises; product quality; quality management system; industry